2018
DOI: 10.3389/fmicb.2018.00166
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Reticulocyte Preference of Two Plasmodium berghei Strains during Blood-Stage Malaria Infection

Abstract: The blood-stage of the Plasmodium parasite is one of the key phases within its life cycle that influences disease progression during a malaria infection. The efficiency of the parasite in infecting red blood cells (RBC) determines parasite load and parasite-induced hemolysis that is responsible for the development of anemia and potentially drives severe disease progression. However, the molecular factors defining the infectivity of Plasmodium parasites have not been completely identified so far. Using the Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Therefore, using flow cytometry to objectively define the erythrocyte populations, we performed comprehensive in vivo tropism measurements for the major rodent malaria strains. Our results broadly agree with previous observations: PbA and Py1.1 have a strong reticulocyte preference ( Fahey and Spitalny, 1984 ; Deharo et al., 1996 ; Cromer et al., 2006 ; Otsuki et al., 2009 ; Martín-Jaular et al., 2013 ; Thakre et al., 2018 ), PccAS has a mixed tropism ( Jarra and Brown, 1989 ), and PvvS67 has a slight normocyte tropism ( Viens et al., 1971 ; Vigário et al., 2001 ). An important distinction between the present study and those before is that we only strictly compared normocytes with the earliest stages of reticulocytes (which still retain many surface proteins).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, using flow cytometry to objectively define the erythrocyte populations, we performed comprehensive in vivo tropism measurements for the major rodent malaria strains. Our results broadly agree with previous observations: PbA and Py1.1 have a strong reticulocyte preference ( Fahey and Spitalny, 1984 ; Deharo et al., 1996 ; Cromer et al., 2006 ; Otsuki et al., 2009 ; Martín-Jaular et al., 2013 ; Thakre et al., 2018 ), PccAS has a mixed tropism ( Jarra and Brown, 1989 ), and PvvS67 has a slight normocyte tropism ( Viens et al., 1971 ; Vigário et al., 2001 ). An important distinction between the present study and those before is that we only strictly compared normocytes with the earliest stages of reticulocytes (which still retain many surface proteins).…”
Section: Discussionsupporting
confidence: 93%
“…Microscopic evaluations are also subjective, and this problem is compounded by the difficulty of differentiating late-stage parasites in reticulocytes from those in normocytes. More recent tropism studies used flow cytometry to distinguish erythrocyte types by their levels of CD71 expression, but these are constrained to only certain species, like P. berghei ( Dertinger et al., 2000 ; Thakre et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To determine if the growth defect of PbmaLS_05 (−) parasites was due to reduced multiplication rates, we analyzed the parasite growth kinetics in KO-iRBC-infected mice, through a mathematical model. Interestingly, the model suggested that deletion of PbmaLS_05 had a modest effect on the ability of parasites to develop within reticulocytes during the initial stages of infection ( 82 ). Therefore, it is plausible that a minor population of KO parasites that fail to develop within reticulocytes are cleared by the spleen and elicit an immune response that protects against ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Other species such as P. falciparum are thought to target all RBCs equally, although there is evidence for preferential invasion of a subset of cells, especially reticulocytes . A number of models that incorporate more sophisticated details of RBC (reticulocyte) production, and preferential targeting of certain RBC stages have been constructed (eg, Figure ; ). These studies have, in most cases, adopted a structure similar to either the many compartment ODE or the PDE models in Figure , but to capture the age structure of the RBCs rather than the parasites (illustrative model presented in Figure ).…”
Section: Host Control Of Parasite Proliferationmentioning
confidence: 99%